Distinct Yet Connected: A Comparative Review of Lytic Skull Lesion Pathologies (East West Medical College Journal, 2026)
Background:Skull lesions, although rare, diagnostically represent a diagnostically challenging spectrum of pathologies that encompass infectious, benign and malignant. They share various overlapping presentations, such as scalp masses and osteolytic defects, yet their underlying etiologies differ markedly that demand different therapeutic strategies and prognosis. Methods: The literature review presents a comparative analysis of three distinct cases: calbvarial tubercular osteomyelitis in a 14 year old female, angiomatous meningioma in a 72 year old male, and metastatic follicular thyroid carcinoma in a 54 year old female. Each case is examined and evaluated alongside relevant literature to delineate the key distinctions in epidemiology, imaging, histopathology, management and outcomes. This review compares epidemiology, pathogenesis, clinical and radiological features, diagnostic approach, management, and prognosis for these three entities, emphasizing distinguishing features and practical diagnostic algorithms. Reporting follows PRISMA 2020 principles for literature identification and reporting.  Findings: Tubercular osteomyelitis typically affects younger individuals and presents with granulomatous inflammation and lytic skull lesions; it responds well to timely anti-tubercular therapy with or without surgery. Angiomatous meningioma, a rare WHO grade 1 subtype shows prominent vascularity and peritumoral edema, is histologically benign, and complete surgical excision shows a cure. Conversely, skull metastases from follicular thyroid carcinoma are rare, aggressive and show poor outcome often requiring multimodal strategies including radioactive iodine, thyroid hormone suppression and surgery. Conclusion: These cases underscore the importance of accurate differentiation of skull lesions and their reliance on a high index of clinical suspicion, supported by detailed imaging and histopathology. Early diagnosis and accurate differentiation of the lesions are critical for management. The cases discussed highlight the pathological variation and the importance of appropriate management to improve patient outcomes.EWMCJ Vol. 14, No. 1, January 2026: 78-86